Tantangan dan Peluang Gen Z Menjadi Agripreneur di Era Marketplace Digital - Setiana, Elia; Budiman; Nur Alamsyah; S.W. Manurip, Atanasius Angga (Pusat Studi Teknologi Informasi Fakultas Ilmu Komputer Universitas Bandar Lampung, 2025)
Generation Z, raised in the digital era, holds significant potential to drive transformation in the agricultural sector through agripreneurship. However, alongside the rapid development of technology and digital marketplaces, they also face various notable challenges. This study explores the barriers faced by Gen Z in initiating and developing agribusiness ventures, including limited access to capital, lack of technical agricultural knowledge, and insufficient mentorship from industry players. On the other hand, there are numerous opportunities to seize, such as easier market access through digital platforms, rising consumer demand for healthy and organic products, and increasing government support for agricultural startups. By adopting adaptive, innovative, and collaborative approaches, Gen Z has a promising opportunity to become a key agent of change in building a modern and sustainable agricultural sector. This study aims to provide insights and strategic recommendations for stakeholders to encourage the emergence of young digital-based agripreneurs in Indonesia.